Determinants of Liquidity and its Relationship with Profitability – The Case of Macedonian Banking Sector - Gockov, GJorgji; Hristovski, Goran (My University, 2019)
This paper deals with the liquidity and profitability of the Macedonian banking sector and attempts to identify the determinants of liquidity mainly focusing on the relationship between profitability and liquidity. First, we analyzed the level of liquidity and profitability and we found that the Macedonian banking system is characterized by high liquidity and relatively high profitability compared with the banking systems of the countries in the region and the more developed economies. Furthermore, the paper examines the determinants of liquidity. The empirical analysis is carried out through the use of the dynamic panel analysis based on the generalized method of moments (GMM) methodology on a dataset of overall banking sector operating in Macedonia in the period from 2007 to 2017. The study uses seven factors as potential determinants of banks liquidity, five of them are internal banks variables (lagged value of liquidity, bank profitability, size of the bank, capital adequacy and non-performing loans) while two of them are macroeconomic variables (GDP growth rate and Central bank reference interest rate). The study showed that profitability is one of the most important factors influencing liquidity in the Macedonian banks. The other determinants with important positive effects on liquidity are lagged value of liquidity, non-performing loans and Central bank interest rate but, to a somewhat lower extent. On the other hand, only the size of the bank is significantly inversely associated with bank liquidity. The capital adequacy and GDP growth rate are not statistically significant factors of Macedonian banks liquidity.
Keywords: Liquidity,Profitability,Determinants,Macedoniancommercialbanks,Paneldataanalysis,GMMmodel